1988
DOI: 10.1038/bjc.1988.67
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-associated trypsin inhibitor (TATI) in ovarian cancer

Abstract: Summary Tumour-associated trypsin inhibitor (TATI) is a 6 kD peptide isolated from the urine of a patient with ovarian cancer. Increased urinary excretion of TATI has earlier been observed in patients with gynaecological malignancies. The value of TATI in urine and serum as a marker for ovarian cancer was studied in 102 patients. Preoperatively urine TATI was elevated in 55% (18/33) and serum TATI in 27% (12/45) of the patients. In patients with mucinous tumours, elevated preoperative levels of TATI were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 14 publications
(19 reference statements)
0
31
1
Order By: Relevance
“…In a study comparing SPINK1 with several other markers, including CA125, SPINK1 was found to be particularly useful for diagnosis of ovarian cancer (16 ). During patient monitoring, the serum concentrations of SPINK1 reflect the development of recurrent disease (17 ). Compared to serum concentrations, up to 1000-fold higher concentrations of SPINK1 have been found in cyst fluid from both benign and malignant ovarian cysts, but increased serum concentrations are rare in patients with benign cysts (18 ).…”
Section: Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In a study comparing SPINK1 with several other markers, including CA125, SPINK1 was found to be particularly useful for diagnosis of ovarian cancer (16 ). During patient monitoring, the serum concentrations of SPINK1 reflect the development of recurrent disease (17 ). Compared to serum concentrations, up to 1000-fold higher concentrations of SPINK1 have been found in cyst fluid from both benign and malignant ovarian cysts, but increased serum concentrations are rare in patients with benign cysts (18 ).…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Claudin-5 is a tight junction protein and its expression is associated with poor prognosis; it was suggested that claudin-5 could influence the expression of SPINK1 and CA125 but this remains to be investigated. Patients with ovarian cancer have higher SPINK1 concentrations in urine than in serum, but they correlate strongly if the urine concentrations are normalized according to urine creatinine or density (13,17 ). The interindividual variation in serum concentrations of SPINK1 are smaller and therefore serum measurements are preferred for follow-up of cancer patients (20 ).…”
Section: Ovarian Cancermentioning
confidence: 99%
“…TATI in serum was measured by radioimmunoassay using reagents from Orion Diagnostica (Oulunsalo, Finland) as described previously (27). A cutoff value of 22 g/liter was used (36). Trypsinogen-2 (34) and trypsin-2-API (37) in serum were measured by timeresolved immunofluorometric assays as earlier described using cutoff values of 80 and 14 g/liter, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Tumour-associated trypsinogen is also known to be a serine protease produced by malignant tumour cells, and is believed to play an essential role in cancer invasion and metastasis by degrading trypsin-sensitive extracellular matrix components (Tryggvason et al, 1987;Koivunen et al, 1991a). Tumour-associated trypsinogen has been identified as a target protease for a tumour-associated trypsin inhibitor (TATI), also referred to as PSTI (Huhtala et al, 1982;Halila et al, 1988;Stenman et al, 1988). A recent study (Koivunen et al, 1989) has shown that tumourassociated trypsinogen and pancreatic trypsinogen are similar with respect to amino-terminal sequence, molecular weight and immunoreactivity, but that significant differences exist with respect to isoelectrophoretic mobility and stability.…”
mentioning
confidence: 99%